Development Students' Thrift Skills in Solving of Tasks - Mukhammedovich, Kosimov Fayzullo (International Journal of Human Computing Studies, 2022)
This article discusses ways to build and develop thrift skills in elementary school students in the process of solving problems in mathematics.